Impacts of social capital on transformation from efficiency to innovation-driven business - Laužikas, Mindaugas; Dailydaitė, Simona (Journal of Business Economics and Management, 2014)
The present article is focused on impacts of social capital on transformation from efficiency to innovation-driven business. Such aspects of social capital as social relations, usage of human capital in innovation processes, expertise in market analysis are often ignored by entrepreneurs. The research purpose is to analyse the relation between social capital and transformation from efficiency to innovation-driven business. Main aspects of this relation are revealed by interpreting findings of Global Entrepreneurship Monitor (GEM), which is to examine how different factors encourage economic development globally via entrepreneurship. Relying on a solid GEM methodology, which combines quantitative adult survey and qualitative expert interviews, various transformation problems of catching-up countries are analysed while paying a special attention to effects of social capital and illustrating them by the case of Lithuania. The role of human capital is measured by such factors as anticipated growth of headcount within respondents’ firms; social relations refer to social image of entrepreneurs (as it is impossible to have a strong social image without good social relations with stakeholders), while information/ knowledge diffusion is analysed via such effects as a number of companies that deliver innovative products and/or services, a number of customers who appreciate and want to try innovative products and/or services as well as a number of expected competitors in the market (it is impossible to be innovative and competitive in the market without information/ feedback collection system established).